On Lamb Waves in a Thermoelastic Plate in the Presence of IdealFluid with Varied Temperature (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In this paper,we studied the phenomenon of wave motion in a homogeneously isotropic, thermoelastic solid plate framed with ideal fluid layers on its both sides with varying temperatures. In the light of the classical theory of thermo-elasticity, all the work is carried out and for Lamb-type thermoelastic wavespropagating in the plate,the secular equations are gobbled up for symmetric and skew-symmetric wave style. The different cases of secular equations are also discussed in the framework of the uncoupled thermo-elasticity.The dispersion equations for three different regions are also deduced.  It is found that the SH mode remains unaffected by thermal variations and keeps itself isolated from the rest of the coupled motion of elastic waves (longitudinal and SV modes) and thermal waves (T-mode).Onewave in each liquid layer also exists due to the presence of ideal fluid loadings. The numerical resultsfor an aluminum-epoxy materialcladded with water are carried out. A wide range of scopes of this research area is available in various fields such as ultrasonics, earthquake engineering, soil dynamics, seismology, etc.